(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
Ecological friendly products increasing plant productivity, quality and resistance against diseases are widely used in biological agriculture many years. One of such products is lignosilicon. That is developed by Latvian State Institute of Wood Chemistry on the basic of wood processing waste and patented. However up to now effect of lignosilicon on the development of winter rye was not tested. Therefore LLU agency “Zemkopības zinātniskais institūts” (Crop-growing Research Institute) carried out investigation of lignosilicon effect on the winter rye “ Duoniai “ cultivation on the certified biological field. In spring 2004 “Lignosilicon” was introduced in soil ( 120 kg/ha ) and red clover “ Divaja “ was sown on the some field. The harvest of grain and straw, length and diameter of stem, ear length, numbers and mass o f grain in ear increased on the background of lignosilicon.